The New Wave of Currency Devaluations in Africa – Will the Devalued Birr Help the Coffee Exports? - Pásztor, Szabolcs (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
Despite the fact that currency devaluations are likely to have a negative effect on the economy in the long run, Ethiopia devalued its national currency, the birr (ETB), by 15 percent in 2017. They turned to this option in the hope of attracting more investments from abroad, decreasing import bills, improving the current account deficit and giving a boost to the exports of the coffee sector. A couple of months later, the impact seems to be promising because the export has been revived in some areas. However, it has to be stressed that the imported commodities may experience a price increase, there can be a widening balance of payments deficit and rising inflation. The paper aims to shed more light on the short- and long-term impacts of currency devaluations in the developing countries with a special emphasis on Ethiopia. Also, the recent Ethiopian measure is to be analyzed in greater detail highlighting the impacts on export earnings, import bills, the balance of payments, and on the overall competitiveness of the coffee sector.